The association between adverse childhood experiences and mental disorders among adolescents in Kenya, Indonesia, and Vietnam: Evidence from the National Adolescent Mental Health Surveys - Yohannes Dibaba Wado; Anne Njeri; Sally Atieno Odunga; Isaiah Akuku; Amirah Ellyza Wahdi; Shoshanna L. Fine; Astha Ramaiya; Mengmeng Li; Vu Manh Loi; Joemer C. Maravilla; James G. Scott; Holly E. Erskine; et al. (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Few studies have examined the prevalence of adverse childhood experiences (ACEs) among adolescents living in low- and middle-income countries, and fewer assessed the association with mental disorders. Methods We used data from nationally representative household surveys of mental disorders among adolescents aged 10–17 years conducted in Kenya, Indonesia, and Vietnam. The lifetime experience of 13 ACEs was measured using a self-administered questionnaire. Mental disorders were measured using a diagnostic instrument. The proportion of adolescents who endorsed each individual ACE, as well as those who endorsed one or more and four or more ACEs, was calculated. Multivariable logistic regression was used to examine the associations between the number of ACEs endorsed and any mental disorder in the past 12 months, after adjusting for demographic characteristics and primary caregiver mental health. Results The prevalence of experiencing at least one ACE was evident among adolescents in all three countries, with Kenya (65.8%, 95% CI: 63.0–68.5) demonstrating significantly higher prevalence than Indonesia (40.2%, 95% CI: 36.4–44.1) and Vietnam (36.9%, 95% CI: 33.1–40.8). Significant differences were seen between all countries in the prevalence of adolescents who experienced four or more ACEs (Kenya: 19.3%, 95% CI: 17.5–21.2; Indonesia: 7.6%, 95% CI: 6.3–9.1; Vietnam: 5.2%, 95% CI: 4.2–6.3). The odds of experiencing a mental disorder in the past 12 months increased as the number of ACEs increased in all three countries. This was most apparent among those experiencing four or more ACEs, who had the highest odds of any mental disorder in the past 12 months as compared to those reporting no ACEs (Kenya: aOR 4.57, 95% CI: 3.35–6.23; Indonesia: aOR 11.10, 95% CI: 6.24–19. 73; Vietnam: aOR 10.30, 95% CI: 5.96–17.82). Conclusion The current study demonstrated that ACEs are common among adolescents in Kenya, Indonesia, and Vietnam, and are significantly associated with mental disorders in all three countries. The prevention of ACEs may be a key avenue for reducing the risk of mental disorders in adolescence.